Rāingān kāntittām læ pram̄œnphon kānčhatngan chal̄œm prakiāt Somdet Phranāng Čhao Phrab̨̄orommarāchinī Nāt n̄ưang nai ōkāt phrarātchaphithī mahāmongkhon chal̄œm phrachonmaphansā 6 r̨ōp 12 Singhākhom 2547 - Sirikit, Queen, consort of Bhumibol Adulyadej, King of Thailand, 1932- (ʻAmarin Phrinting ʻ̄æn Phaplitching, 2005)
Report on the celebrations, projects, ceremonies, and activities commemorating the 72nd birthday of Queen Sirikit of Thailand.